A Comparative Study of Human-Nature Relationship in Indonesian and Japanese Folklore - Hartawan, Ni Putu Zefanya Putri Gracia (Universitas Negeri Semarang, 2024)
Human and nature are inseparable as they become a unit and interchange with each other where both of relationships are also described in a lot of literature everywhere. In Indonesia, the depictions of the relationship are told through folklore. La Moelu from Southeast Sulawesi tells a story about a boy who kept his fish that he caught from fishing, took care of it, and the fish granted him a reward. There's also a Japanese folklore about a man who saved a wounded crane and it returned him a favor for the assistance, called Tsuru no Ongaeshi. As these two stories similarly talk about men-nature relation, this research aims to compare the cultural background and the mutual relationship between men and nature. The analysis will be done through the first wave of ecocriticism perspective. This research reveals that both of the main characters from those stories have attempted to preserve nature. However, when greed seeps into men's consciousness, they become less considerate of the environment and have to face the consequences of their actions. This research demonstrates the men-nature relation through folklore as a way to show individuals' dynamic reactions and behavior towards nature to uncover nature's imbalance when human attitudes deviate.